Changes In Rocket Salad Phytochemicals Within The Commercial Supply Chain: Glucosinolates, Isothiocyanates, Amino Acids And Bacterial Load Increase Significantly After Processing - Hanis Nadia Yahya; Luke Bell; Omobolanle Oluwadamilola Oloyede; Lisa Methven; Carol Wagstaff (Elsevier, 2024)
Five cultivars of Eruca sativaand a commercial variety of Diplotaxis tenuifolia were grown in the UK (summer) and subjected to commercial growth, harvesting and processing, with subsequent shelf life storage. Glucosinolates (GSL), isothiocyanates (ITC), amino acids (AA), free sugars, and bacterial loads were analysed throughout the supply chain to determine the effects on phytochemical compositions. Bacterial load of leaves increased significantly over time and peaked during shelf life storage. Significant correlations were observed with GSL and AA concentrations, suggesting a previously unknown relationship between plants and endemic leaf bacteria. GSLs, ITCs and AAs increased significantly after processing and during shelf life. The supply chain didnot significantly affect glucoraphanin concentrations, and its ITC sulforaphane significantly increased during shelf life in E.sativacultivars. We hypothesise that commercial processing may increase the nutritional value of the crop, and have added health benefits for the consumer.